Procurement Process of Goods and Dental Polyclinic Unit Space Batang Hospital in the Era of the Covid 19 Pandemic (Case Study) - Inneke Kencana Sari; Iwan Dewanto; Firman Pribadi (Budapest International Research and Critics University, 2022)
The implementation of the procurement of medical devices and the layout of the dental polyclinic unit is an important factor in supporting health service efforts. Procurement of medical equipment and spatial planning requires additional budget, this is due to adjustments that must be carried out by the dental polyclinic unit of Batang Hospital. The purpose of this study was to determine the process of implementing procurement of goods and adjusting the layout of the dental polyclinic unit of the Batang Regional General Hospital in the Covid 19 pandemic era. Method: The study used a qualitative method (case study). The research subjects were employees of RSUD Batang totaling 7 respondents and 2 respondents triangulation with total sampling technique. Data analysis using a qualitative interactive model Research Results: The implementation of the proposal, planning, budgeting, procurement and spatial adjustment of the dental polyclinic unit has been going well and in accordance with the procedure, although it is not perfect as for the need for proposing medical equipment, it is not fully in accordance with the needs of the dental clinic. Barriers to procurement of goods and adjustments to the layout of the dental polyclinic unit are caused by limited budgets or not in accordance with realization, so that the proposed needs are considered according to a priority scale. The risk of procurement of goods and adjustments to the layout of the dental polyclinic unit that has not been fulfilled, the management is responsible in this case to reduce the risk by providing level 3 PPE, vaccines and other forms of protection with assistance. Conclusion: The process of implementing the procurement of goods and adjusting the layout of the dental polyclinic unit of the Batang Regional General Hospital in the era of the Covid 19 pandemic has been going well and not fully in accordance with the needs of the user/dentist.